Bioengineered Approach to the Design of a Fat Graft Based on Mathematical Modeling that Predicts Oxygen Delivery. Issue 6 (June 2019) - Suszynski, Thomas M.; Rohrich, Rod J.; Sieber, David A.; Boyd, Travis G.; Thornton, James F.; Teotia, Sumeet S.; Cunningham, Bruce L.; Van Beek, Allen L.
Abstract : Background: Fat grafting is a common procedure in plastic surgery. A major limitation is unpredictable graft retention, in part caused by inadequate oxygen delivery during the early posttransfer period. Methods: The authors present a bioengineered approach to the design of a fat graft based on mathematical theory, which can estimate the limitations of oxygen delivery. To simplify the problem, four variables were defined: (1) recipient-site oxygen partial pressure; (2) adipose tissue oxygen permeability; (3) adipose tissue oxygen consumption rate; and (4) fat graft size. Recipient-site oxygen partial pressure and adipose tissue oxygen permeability were estimated from literature, whereas adipose tissue oxygen consumption rate was measured using stirred microchamber technology. Calculations were performed in both spherical and planar geometry to calculate the maximum allowable fat graft size from an oxygen delivery standpoint. Results: As expected, planar geometry is less favorable for oxygenation but represents a realistic configuration for a fat graft. Maximum allowable fat graft thickness is only approximately 1 to 2 mm at external oxygen partial pressures of 10 to 40 mm Hg; any thicker and an anoxic or necrotic core likely develops. Given a reasonably large surface area and assuming several planes of injection, the maximum allowable fat graft volume is tens of milliliters. Conclusions: A systematic bioengineered approach may help better design a fat graft. Applying principles of mass transfer theory can predict whether a fat graft has a favorable chance of surviving from an oxygen delivery standpoint and can direct the development of strategies for improved fat graft oxygenation.